A Quick Guide to Software Licensing for the Scientist-Programmer - Morin, Andrew; Urban, Jennifer; Sliz, Piotr (PLoS computational biology, 2012)
[...]proprietary licenses are often very restrictive for end-users. [...]in our software-dependent information age, few laws are influencing our professional (and personal) pursuits more than these.